The Administrative Empowerment Among School Principals and Its Relationship to School Crisis Management from the Point of View of Teachers A field study in the second cycle schools of basic education in Latakia city - أحمد, خالد; وفيقة علي; نورا محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the degree of administrative empowerment and the degree of school crisis management among principals of schools in the second cycle of basic education from the point of view of teachers, as well as identifying the relationship between administrative empowerment and school crisis management among principals of schools in the second cycle of basic education from the point of view of teachers in Latakia city. It included: The research sample includes (258) teacher. To achieve the purpose of the research, two questionnaire tools were built, the first consisting of (34) statements that measure the degree of administrative empowerment among managers, divided into five axes: (communication and communication, delegation of powers, collective work teams, collective work teams, participation in decision-making, and self-efficacy). And a second questionnaire consisting of (26) statements measuring school crisis management among principals. The results of the research showed that the degree of administrative empowerment among school principals in the second cycle of basic education, from the point of view of teachers, was average, and that the degree of school crisis management among them was also average. The results also showed that there was a good direct and statistically significant relationship between administrative empowerment and school crisis management among school principals. The second cycle of basic education from the teachers’ point of view School crisis management can be predicted through the axes of administrative empowerment (communication and communication, delegation of powers, collective work teams, participation in decision-making, and self-efficacy). The research also presented proposals, including training principals on appropriate administrative empowerment for their school, and giving them the necessary powers to make appropriate decisions to confront the crises facing them, as well as administrative empowerment and school crisis management in other samples and in other educational environments and stages.